Resection of Anaplastic Meningioma via Combined Craniofacial Approach - Yosafat Kurniawan Sugiarto; Arwinder Singh; Muhammad Firdaus; Oskar Ady Widarta; Farilaila Rayhani (Indonesian Journal of Cancer, 2022)
Introduction: Meningiomas are common and mostly benign intracranial tumors but may show a histological progression to malignancy. The mechanism of malignant transformation remains unclear. Malignant meningiomas usually bear a high recurrence rate and unfavorable prognosis; hence, multiple surgical resections are required for the treatmentCase Presentation: A 41-year-old woman with a prior history of craniotomy at another center six years ago with Meningioma Grade 1 presented to our institution with new neurological symptoms. The magnetic resonance image demonstrated a large frontal base mass that extended to the nasal cavity with diffuse contrast enhancement and extensive surrounding edema. A craniofacial approach combined with a bifrontal approach was performed in multistage tumor resection. The tumor and the infiltrated dura were radically removed. The histopathology demonstrated an Anaplastic Meningioma. The patient also underwent radiation therapy.Conclusion:  Treatment of recurrent meningioma with anaplastic histology remains challenging because recurrence rates remain high with a poor prognosis.